SIKAP TERHADAP BIMBINGAN SOSIAL PADA PENERIMA MANFAAT DI PANTI SOSIAL BINA REMAJA (PSBR) RUMBAI KOTA PEKANBARU - Adilah, Sausan; Natuna, Daeng Ayub; Irja, Desti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is 1) to know attitudes toward social guidance on beneficiaries based on demographic factors, 2) to know the level of attitudes toward social guidance on beneficiaries in juvenile social institution (PSBR) of Pekanbaru, 3) to know contribution information service to orientation service and contribution to social guidance attitude to beneficiary in social institution of adolescent development (PSBR) of rumbai city of Pekanbaru. This research is descriptive research with quantitative approach. The population in this study are all beneficiaries who follow the social guidance material in the Social Institution of Youth Development (PSBR) Rumbai Pekanbaru City which amounted to 70 respondents. The sampling technique in this research is using a simple technique saturated (Surve) that is taking the sample members of the population done as a whole without regard to the strata in the population. The instruments in this study are questionnaires or questionnaires containing 132 items of questions. Attitudes towards social guidance are measured by indicators of Information Services and Orientation Services. From the results of the research note that Attitudes Against Social Guidance On Beneficiaries in Social Institutions Bina Remaja (PSBR) Rumbai Pekanbaru city is good / positive. the best / positive means of attitude orientation service to social counseling with mean 4.29 and SD 0.60 were then followed by attitudes toward low social guidance ie information service with mean 4.24 and SD 0.61. The meaning is that information services have little effect on social guidance, but orientation services are very influential on social guidance.Keywords: Attitude, Social Guidance, Beneficiaries